2014
DOI: 10.1515/cclm-2013-1124
|View full text |Cite
|
Sign up to set email alerts
|

The association between plasminogen activator inhibitor type 1 (PAI-1) levels, PAI-1 4G/5G polymorphism, and myocardial infarction: a Mendelian randomization meta-analysis

Abstract: Background: The circulating levels of plasminogen activator inhibitor type 1 (PAI-1) are increased in individuals carrying the 4G allele at position -675 of the PAI-1 gene. In turn, overexpression of PAI-1 has been found to affect both atheroma and thrombosis. However, the association between PAI-1 levels and the incidence of myocardial infarction (MI) is complicated by the potentially confounding effects of well-known cardiovascular risk factors. The current study tried to investigate in parallel the associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 56 publications
(56 reference statements)
0
29
0
4
Order By: Relevance
“…Similarly, negative findings have been reported in an elderly cohort. 105 More recently, by using the MR meta--analysis approach, Nikolopoulos et al 106 confirmed a previous observation that the PAI-1 4G allele slightly increases the MI risk.…”
Section: -94mentioning
confidence: 70%
“…Similarly, negative findings have been reported in an elderly cohort. 105 More recently, by using the MR meta--analysis approach, Nikolopoulos et al 106 confirmed a previous observation that the PAI-1 4G allele slightly increases the MI risk.…”
Section: -94mentioning
confidence: 70%
“…As a protein biomarker, the genetic locus encoding the PAI‐1 transcript has clear biological function in determining circulating PAI‐1 levels. The 4G/5G polymorphism in the promoter region of SERPINE1 has been consistently reported to be a functional variant influencing PAI‐1 expression 27, 49. Knockout of Serpine1, a mouse ortholog, creates PAI‐1 deficiency 50.…”
Section: Discussionmentioning
confidence: 99%
“…Given that genotypes are assigned randomly from parents to offspring during meiosis, the causal effect of PAI‐1 on CHD risk can be estimated by the ratio of a SNP(IV)‐PAI‐1 association to SNP(IV)‐CHD association 25, 26. Using the MR method, a previous study suggested a causal association of PAI‐1 with myocardial infarction and blood triglycerides 27. However, in that study, the association of the SNP, the “4G/5G” polymorphism (rs1799889) in SERPINE1, with PAI‐1 and CHD risk was based on a meta‐analysis using published candidate gene studies between 1993 and 2010 27.…”
Section: Introductionmentioning
confidence: 99%
“…These facts may partly explain the discrepancies between our index data and previously reported evidence. A recent, elegant meta-analysis study suggested that polymorphisms in the gene encoding PAI-1 increased the risk of myocardial infarction, resulting in increased PAI-1 activity [23]. Importantly, PAI-1 levels were associated with a higher risk of restenosis and ST after DES implantation [24].…”
Section: Discussionmentioning
confidence: 99%